Infrared Spectra of 2-Amono-4,6-Dichloro Pyrimidine - Sharma, V.K.; Kumar, Praveen; Sharma, S.D. (Asian Journal of Chemistry, 2010)
The IR spectra of 2-amino-4,6-dichloropyrimidine have beenrecorded on Perkin-Elmer spectrophotometer in the region 4000-200 cm-1 using KBr-pellet technique. The spctrum has been analysedassuming C2v point group symmetry for the molecule. Theprobable assignments to the obeserved fundamental frequency withstructural features have been assigned to different modes of vibrationson the basis of magnitude and relative intensity of the recordedspectra and group frequency appioach with analogy to the similarmolecules.